A Pilot Study of Metabolomic Pathways Associated With Fatigue in Survivors of Colorectal Cancer. Issue 1 (January 2021) - Chou, Yun-Jen; Kober, Kord M.; Kuo, Ching-Hua; Yeh, Kun-Huei; Kuo, Tien-Chueh; Tseng, Yufeng J.; Miaskowski, Christine; Liang, Jin-Tung; Shun, Shiow-Ching
Background: Over 30% of cancer survivors experience chronic fatigue. An alteration in energy metabolism is one of the hypothesized mechanisms for cancer-related fatigue (CRF). No studies have evaluated for changes in metabolic profiles in cancer survivors with CRF. The purpose of this pilot study was to evaluate for differences in metabolic profiles between fatigued and non-fatigued survivors of colorectal cancer (CRC). Methods: Survivors were recruited from the surgical outpatient department and the oncology clinic of a medical center in northern Taiwan. Fatigue was assessed using the Fatigue Symptom Inventory. Fasting blood samples were collected on the day the fatigue questionnaire was completed. Metabolomic profile analysis was performed using non-targeted, liquid chromatography/time-of-flight mass spectrometry. Fold change analyses, t-tests, and pathway analyses were performed to identify differences in metabolomic profiles between the fatigued and non-fatigued survivors. Results: Of the 56 CRC survivors in this study, 28.6% (n = 16) were in the fatigue group. Statistically significant differences in carnitine, L-norleucine, pyroglutamic acid, pyrrolidonecarboxylic acid, spermine, hydroxyoctanoic acid, and paraxanthine were found between the two fatigue groups. In addition, two pathways were enriched for these metabolites (i.e., glutathione metabolism, D-glutamine and D-glutamate metabolism). Conclusions: Findings from this pilot study provide preliminary evidence that two pathways that are involved with the regulation of ATP production and cellular energy (i.e., glutathione metabolism, D-glutamine and D-glutamate metabolism) are associated with fatigue in CRC survivors. If these findings are confirmed, they may provide new therapeutic targets to decrease fatigue in cancer survivors.